2020
DOI: 10.1002/jcsm.12548
|View full text |Cite
|
Sign up to set email alerts
|

Fat‐to‐muscle ratio as a predictor of insulin resistance and metabolic syndrome in Korean adults

Abstract: Background The present study evaluated the associations of the fat‐to‐muscle ratio (FMR) with metabolic syndrome (MetS) and insulin resistance (IR) in Korean adults using nationally representative survey data. Methods A two‐stage stratified sampling method was reflected in a cross‐sectional study involving a total of 13 032 participants aged ≥ 19 years who participated in the fourth and fifth Korea National Health and Nutrition Examination Surveys. The homeostasis model assessment for IR (HOMA‐IR) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 56 publications
5
73
2
1
Order By: Relevance
“…Therefore, during skeletal muscle aging there will be an increase in insulin resistance that leads to T2DM. An interesting study by Seo et al 28 reported relationship of fat to skeletal muscle mass ratio with insulin resistance indices and MetS. Similar to our observations there was a significant association of this ratio with insulin resistance and it could be a novel marker for detecting MetS, both in normal weight and obese people.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, during skeletal muscle aging there will be an increase in insulin resistance that leads to T2DM. An interesting study by Seo et al 28 reported relationship of fat to skeletal muscle mass ratio with insulin resistance indices and MetS. Similar to our observations there was a significant association of this ratio with insulin resistance and it could be a novel marker for detecting MetS, both in normal weight and obese people.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, studies have linked sarcopenia obesity with insulin resistance, dyslipidemia, and T2D, which all implicated in the development of NAFLD [ 34 ]. Meanwhile, it has been reported that the FM/FFM ratio was positively associated with insulin resistance in the general population and liver fat accumulation, which was an important pathological feature of NAFLD, in patients with T2D directly [ 18 , 35 ]. Besides, studies also suggested that the FM/FFM ratio was capable to be regarded as a novel predictor of metabolic syndrome and glucose metabolic disorder, which both were associated closely with NAFLD [ 18 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it has been reported that the FM/FFM ratio was positively associated with insulin resistance in the general population and liver fat accumulation, which was an important pathological feature of NAFLD, in patients with T2D directly [ 18 , 35 ]. Besides, studies also suggested that the FM/FFM ratio was capable to be regarded as a novel predictor of metabolic syndrome and glucose metabolic disorder, which both were associated closely with NAFLD [ 18 20 , 36 ]. Combined these studies with the findings of our study, the FM/FFM ratio could be a useful predictor of the risk of developing NAFLD among different obesity status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Развитие ОП у женщин с наcтуплением периода менопаузы тесно связано с метаболическим синдромом Оригінальні дослідження / Original Researches (МС), или синдромом инсулинорезистентности Х [6,7], при котором накопление конечных продуктов гликирования приводит к усилению ломкости костей [8,9]. МС не только ухудшает течение ОП у неменструирующих женщин, но и снижает эффективность мероприятий по вторичной профилактике остеофрактур, что требует совершенствования лечебных мероприятий у таких больных [10].…”
Section: Introductionunclassified